2021
DOI: 10.1186/s13017-021-00377-w
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid emergency rooms reduce the requirement of blood transfusion in patients with severe trauma

Abstract: Background A hybrid emergency room (ER) is defined as an emergency unit with four functions—performing resuscitation, computed tomography (CT), surgery, and angiography. However, the safety and efficacy of performing CT in a hybrid ER are unclear in primary surveys. Therefore, this study aimed to evaluate the safety and clinical effects of hybrid ERs. Methods This retrospective observational study used data from the Shimane University Hospital Trau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Notably, the use of diagnostic modalities such as computerized tomography (CT) and angiography is limited in patients with unstable vital signs. To overcome this, a hybrid emergency room (ER) equipped with a CT machine and operating theater has been established and used for unstable patients [ 3 ]. However, many trauma centers in Korea operate without a hybrid ER.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the use of diagnostic modalities such as computerized tomography (CT) and angiography is limited in patients with unstable vital signs. To overcome this, a hybrid emergency room (ER) equipped with a CT machine and operating theater has been established and used for unstable patients [ 3 ]. However, many trauma centers in Korea operate without a hybrid ER.…”
Section: Introductionmentioning
confidence: 99%
“…The hybrid ER can be used for performing CT imaging, endovascular treatment, and emergency surgery including DCS without moving the patient, making it more effective for prompt diagnosis and treatment of hemodynamically unstable patients [1][2][3]. Hemodynamic instability in endogenous diseases can be caused by various factors such as hemorrhage, sepsis, and obstructive shock.…”
Section: Discussionmentioning
confidence: 99%
“…We were the rst in the world to introduce a rotary table hybrid ER system in 2017 [2]. Additionally, we reported that treatment in the hybrid ER contributed to a reduction in blood transfusion doses in patients with severe trauma [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant association was found between the hybrid ER and decreased mortality (adjusted odds ratio [aOR], 0.50; 95% confidence interval [CI], 0.29-0.85; p = 0.011) and reduced deaths from exsanguination (aOR, 0.17; 95% CI, 0.06-0.47; p = 0.001). The times to initiation of CT and emergency bleeding control procedures were also both shorter in the hybrid ER group versus the Conventional group (11 [8-16] vs. 26 [21][22][23][24][25][26][27][28][29][30][31][32] The first retrospective observational study on blood transfusion amounts during resuscitation in the hybrid ER was reported by Watanabe et al The amount of blood transfused was significantly lower in the hybrid ER versus nonhybrid ER group (whole blood: 8 vs. 14 units, p = 0.004; red blood cells: 2 vs. 6 units, p = 0.012; fresh frozen plasma: 6 vs. 9 units, p = 0.021). 29 This difference remained after propensity score matching (whole blood: 6 [4-16.5] vs. 28 units, p = 0.015; red blood cells: 2 [0-8.5] vs. 8 [2.75-26.5] units, p = 0.020; fresh frozen plasma: 6 [3.5-7.5] vs. 18 [5.5-27] units, p = 0.057).…”
Section: Clinical Experience With Severe Trauma In the Hybrid Ermentioning
confidence: 99%